2007
DOI: 10.2478/s11536-007-0010-x
|View full text |Cite
|
Sign up to set email alerts
|

A case with full clinical manifestations of Dorfman-Chanarin syndrome

Abstract: AbstractDorfman-Chanarin syndrome (DCS), is a rare, autosomal recessive disorder associated with lipid metabolism. It is characterized by ichthyosiform nonbullous erythroderma, lipid vacuoles in peripheral leukocytes and variable involvement of organs. We report a Turkish man with the complete syndrome, who described family history of ichthyosis. To best of our knowledge this is the sixth case from Turkish origin to date. In addition to congenital ichthyosis he had also strabis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…We reviewed the original cases of CDS published in peer-reviewed journals [9][10][11][12][13][14][15][16], and found that liver involvement is the second most common clinical manifestation after ichthyosis, with abnormal liver enzyme levels being documented in about 78% of the patients. However, end-stage liver disease has so far been described in only six cases (15%) including our own.…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed the original cases of CDS published in peer-reviewed journals [9][10][11][12][13][14][15][16], and found that liver involvement is the second most common clinical manifestation after ichthyosis, with abnormal liver enzyme levels being documented in about 78% of the patients. However, end-stage liver disease has so far been described in only six cases (15%) including our own.…”
Section: Discussionmentioning
confidence: 99%
“…This syndrome is associated with multiple organ involvement. Other clinical findings aside from ichthyosis include hepatomegaly, bilateral ectropion, cataract, muscle weakness, bilateral sensorineural deafness, splenomegaly, short stature, small ears, strabismus and mental retardation 64–74 . In addition, clinical findings, such as microcephaly, cardiomyopathy, nystagmus, eclabion, rickets, renal eccrine gland and pancreatic involvement, are also observed in rare cases 75–80 .…”
Section: Discussionmentioning
confidence: 99%
“…Other clinical findings aside from ichthyosis include hepatomegaly, bilateral ectropion, cataract, muscle weakness, bilateral sensorineural deafness, splenomegaly, short stature, small ears, strabismus and mental retardation. [64][65][66][67][68][69][70][71][72][73][74] In addition, clinical findings, such as microcephaly, cardiomyopathy, nystagmus, eclabion, rickets, renal eccrine gland and pancreatic involvement, are also observed in rare cases. [75][76][77][78][79][80] The most common clinical findings in patients were ichtyosis 100% and hepatomegaly 60%, and the others were bilateral ectropion, cataract, neurosensory deafness and splenomegaly (29%, 22%, 17% and 13% respectively).…”
Section: Liver Disease Liver Phenotype Genotype/mutationmentioning
confidence: 99%